My century - Grass, Gunter 1927-2015 (Harcourt, 1999)
One hundred stories, each named after a year this century. In one, Erich Maria Remarque gives his views on World War I, in another former Nazis reflect on the good old days, while a third is on the fall of the Berlin Wall from a dead woman's point of view.